Macwilliams Identity for M-Spotty Hamming Weight Enumerator Over the Ring F2+vF2 - Siap, Vedat; Ozen, Mehmet (EUROPEAN JOURNAL PURE & APPLIED MATHEMATICS, 2012)
The m-spotty byte error control codes can correct or detect multiple spotty byte errors that are distributed in multiple bytes. These codes are successfully applied to computer memory systems that use RAM chips with b-bit Input/Output data when high-energy particles strike a particular RAM chips. In this paper, we derive a MacWilliams type identity for m-spotty Hamming weight enumerator over the ring F-2 + vF(2) with v(2) = v.
Keywords: MacWilliams identity; Weight enumerator; M-spotty weight; M-spotty byte error; Mathematics